Reliability Analysis and Design of MMC Based on Mission Profile for the Components Degradation - Gaotai Lv; Wanjun Lei; Meng Wang; Chunlin Lv; Jiaqi Zhao (IEEE Access, 2020)
In the field of high voltage level applications, modular multi-level converter (MMC) has the definite advantages of low power loss and modularity and there have been many studies on its reliability. Some researches focus on the degradation of physical characteristics in the lifetime prediction of key devices, but the degradation of physical characteristics has not been directly used in the research of MMC system level reliability. The traditional exponential distribution failure rate is constant while the Monte Carlo method assumes the random distribution of multiple devices. Neither of these two methods can describe the reliability of a single device with physical characteristics degradation. This article presents a system level MMC reliability analysis and design method based on MMC mission profile and insulated-gate bipolar transistor (IGBT) lifetime degradation. According to the IGBT current and power loss in MMC, the annual mission profile and junction temperature result are analyzed by rainflow counting algorithm. In terms of device degradation, the thermal network updating method is used to calculate the life of IGBT in different time, and the reliability analysis method based on exponential distribution is improved. To optimize the redundancy design of the system, the multi-objective function optimization is processed.